2015
DOI: 10.1016/j.procs.2015.12.203
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Augmented Reality in Vocational Education and Training

Abstract: In Vocational Education and Training (VET) institutions, teachers face important difficulties in the teaching process due to a wide variety of student’s special educational needs as well as student’s lack of: the adequate level of basic competence, motivation, concentration, attention, confidence and background knowledge, among other aspects. Regarding the attention to these aspects, many studies have reported positive impact of Augmented Reality (AR) applications in primary, secondary and higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(218 citation statements)
references
References 14 publications
6
129
2
3
Order By: Relevance
“…These types of studies are needed to identify the ideal use of the AR technology in educational environments. It is noteworthy that studies on the use of AR in vocational education and training are insufficient while studies were conducted in various educational fields in the literature (Bacca et al, 2014;Bacca et al, 2015). While there are some studies to develop AR applications for operators and technicians (Ramírez et al 2015;Rios et al 2013;Caudell and Mizell 1992;Reiners et al 1999;Sääski et al 2008;Henderson and Feiner 2009;Tang et al 2003), the number of studies conducted for this purpose in educational environments is rather few.…”
Section: Significance Of the Study And Hypothesesmentioning
confidence: 99%
“…These types of studies are needed to identify the ideal use of the AR technology in educational environments. It is noteworthy that studies on the use of AR in vocational education and training are insufficient while studies were conducted in various educational fields in the literature (Bacca et al, 2014;Bacca et al, 2015). While there are some studies to develop AR applications for operators and technicians (Ramírez et al 2015;Rios et al 2013;Caudell and Mizell 1992;Reiners et al 1999;Sääski et al 2008;Henderson and Feiner 2009;Tang et al 2003), the number of studies conducted for this purpose in educational environments is rather few.…”
Section: Significance Of the Study And Hypothesesmentioning
confidence: 99%
“…Bacca et al (2015) found that it had positive effects on the dimensions of attention, relevance, confidence and satisfaction, which were core contributors to increasing motivation in learning. An ART application with a good design not only enhances the trainees' level of engagement, but also addresses the limitations of one-size-fits-all curricula, and hence supports a more personalized learning experience (Bacca et al, 2015). The pedagogical approach prescribed in ART can be applied in other domains as well.…”
Section: Augmented Reality Training/testing (Art)mentioning
confidence: 96%
“…Bacca et al (2015) introduced an ART application, Paint-cAR, to help students on a vocational training program in car maintenance. Specifically, it engages students to become familiar with the procedural steps for repairing the paint on a car, including safety measures and identification of chemical tools or products.…”
Section: Augmented Reality Training/testing (Art)mentioning
confidence: 99%
“…Recently, the 3D registration for MAR uses GPS and sensors from mobile devices to provide different information about position and pose of the camera and combine them with computer vision to improve the speed and accuracy of the system. Other studies, such as [5] propose a makerbased Mobile Augmented Reality solution. The application is used by a Vocational Educational and Training (VET) program for supporting the maintenance process of a car.…”
Section: Introductionmentioning
confidence: 99%
“…The authors define VET as "education programs that are designed for learners to acquire the knowledge, skills and competencies specific to a particular occupation, trade or class of occupations or trades"(p. 49-50). Moreover, in [5] is presented an AR application used by VET students for basic mathematics skills, which is based on videogames. More studies, such as [6] present a Mobile Augmented Reality solution for learning French language which is based on gamification didactic method.…”
Section: Introductionmentioning
confidence: 99%